Studi Literature Sistem Keamanan Biometrik Untuk Verifikasi dan Transaksi Dompet Digital - Nahrun Hartono; Adhy Rizaldy; NIswa Ayu Lestari (Journal Software, Hardware and Information Technology, 2022)
E-Wallet is a service for storing money electronically that can be used for financial transactions or electronic payments easily and quickly. With the increasing use of digital today, the more the threat of ID theft and account takers can lead to balance withdrawals. In the last few years, fraudulent activities have grown rapidly so that only using a PIN and password with one-time password verification is no longer safe. The solution to this security problem is to use biometric authentication. A biometric security system is an authentication system for unique parts of the human body such as fingerprints, irises, and faces, which are stored in a database. This paper will discuss how the biometric security system is used in verification and transactions on digital wallets.